Interplay of ST2 downregulation and inflammatory dysregulation in hypertrophic cardiomyopathy pathogenesis - Xingyu Cao; Huawei Wang; Zunsong Hu; Zunsong Hu; Wenfang Ma; Peng Ding; Huang Sun; Xiying Guo (Frontiers in Cardiovascular Medicine)
BackgroundHypertrophic Cardiomyopathy (HCM) is an inherited heart disease and the pathogenesis of HCM involves genetic mutations, hemodynamic stress, and metabolic factors, with myocardial fibrosis playing a crucial role in severe clinical events. IL-33/ST2 signaling pathway known for its roles in immune response and tissue repair, participates in cardiac protection and anti-cardiac fibrosis in heart failure. The role of ST2 in HCM remains unclear, and IL-33/ST2 pathway and broader inflammatory responses may be critical in HCM.MethodsWe re-analyzed RNA sequencing data from 9 high-throughput sequencing datasets comprising myocardial tissue samples from 109 HCM patients and 210 non-HCM controls. Differential gene expression analysis, correlation analyses, and Gene Set Enrichment Analysis (GSEA) were employed to explore the biological significance of ST2-related genes and the IL-33/ST2 pathway. Immune infiltration was assessed using CIBERSORTx, and protein-protein interaction networks were constructed using the STRING database.ResultsOur analysis identified 2,660 upregulated and 403 downregulated genes for HCM in the combined dataset, with significant downregulation of the ST2 gene (log2 fold change = −5.0, adjusted P-value = 9.2  ×  10−¹⁴³). This downregulation was consistently observed across multiple individual studies. Correlation analysis revealed significant positive correlations between ST2 and key inflammatory mediators such as IL6 and CD163. GSEA highlighted the enrichment of pathways related to immune response, inflammation, and cardiac morphogenesis, with notable upregulation of pro-inflammatory pathways. Immune infiltration analysis revealed a significant inverse correlation between ST2 expression and regulatory T cells (r = −0.34) and a positive correlation with neutrophils (r = 0.39). Pathway analysis indicated ST2's key role in networks involving inflammatory and fibrotic responses.ConclusionsOur findings suggest that downregulation of ST2 in HCM may be associated with a dysregulated inflammatory gene network, potentially contributing to myocardial fibrosis and remodeling. These results highlight the possible critical role of the IL-33/ST2 pathway in disease progression, offering a potential therapeutic target for managing inflammation and fibrosis in HCM.